AN INVESTIGATION ON CURRENT GREEN DESIGN PRACTICES TOWARDS NET-ZERO ENERGY BUILDINGS (NZEBs) APPLICATION IN MALAYSIA HEALTHCARE PROJECTS - Bin Abdellah, Roy Hazli; Bin Masrom, Md Asrul Nasid; Chen, Goh Kai; Bin Mohamed, Sulzakimin; Binti Manap, Norpadzlihatun (Journal of Technology Management and Business, 2018)
These days, the topic on the sustainable building has become one of the most important concerns in the academic studies, construction industries, as well as governmental agencies. Sustainability in the building sector has raised the attention towards a new concept called net-zero energy buildings (NZEBs). With regards to the development of Malaysia’s buildings sectors, the government has realised the undesirable effects of inefficient of energy usage by demonstrating their efforts in Construction Industry Transformation Programme (CITP) 2016-2020. Commonly, healthcare buildings are among the greatest energy consumers of any institution and the extensive use of various medical equipment, mechanical ventilation of this building has caused a high level of carbon emission. Hence, by concentrating on these issues, NZEBs become an important concept to be implemented in healthcare buildings. However, the awareness of NZEBs in Malaysia is still low and the construction industry in Malaysia still unaware of NZEBs. This paper aims to investigate the current design practices of healthcare buildings in Malaysia as well as the architect’s understanding of NZEBs through preliminary investigation among architects. Literature was reviewed and pilot studies by using semi-structured interviews were conducted. The results uncover that some green practices related to the design practices in healthcare buildings has been carried out and some of these practices are similar to the NZEBs design practices even though the term of ‘NZEBs’ is not being used. It is predicted that the paper will provide a basic knowledge for future research in NZEBs for healthcare buildings, challenges of NZEBs implementation and designing NZEBs for healthcare buildings in Malaysia. Keywords: Net zero energy buildings, Healthcare building, Current green design practices, Malaysia